“Respuesta de la omisión de macronutrientes primarios sobre el desarrollo y rendimiento del cultivo de cacao (Theobroma cacao L.)” - Ayala Páez, Erika Tatiana (2024)
This research was carried out at the "Sacha Wiwa" Experimental Center, in the Guasaganda parish of the La Maná canton with a duration of six months, with the objective of Evaluating the effect of the response to the omission of primary macronutrients on the development and yield of the cocoa crop (Theobroma cacao L.)", for which a completely randomized block design was established, with a factorial arrangement A x B (3 x 5), where factor A corresponds to the cocoa clones (CCN-51, EET-48 and EET-96) and factor B to the omissions of macronutrients (-N), (-P), (-K),(-N, P, K) y (N,P,K), as for the results obtained, factor A obtained the highest averages with clone CCN-51 with a higher number of healthy cob with 5. 60, a lower number of diseased ears with 4.35, a lower disease index with an average of 44.55, a greater ear length of 23.7, with a greater ear diameter of 10.37, weight of 100 seeds with 2.32, a better weight of dry grains with 1.18 g, a greater yield with 378.59 kilograms per hectare. As for factor B, a greater number of healthy cobs with the omission of NPK with four healthy cobs, lower number of diseased cobs with 2.67, better cob diameter with 10.59, better fresh grain weight with 0.70 g; on the other hand, the omission of P obtained better results in terms of lower disease index with 33.38, better yield with 183.08 kg/ha. The omission of K obtained lower results in the research. Consequently, in the economic analysis obtained a better result with clone CCN51 and with the omission of NPK profitability of 102.63%.